Institutions and social mobilization the Chinese education movement in Malaysia, 1951-2011 - Ang, Ming Chee (Institute of Southeast Asian Studies, 2014)
Offers a major contribution since the work of Tan Liok Eee on the Dongjiaozong movement in Malaysia. The author's familiarity with both popular and academic writings in Mandarin has yielded rare, first-hand, and often bottom-up views on the Dongjiaozong movement from actors directly involved in the movement.